Effectiveness of Tax Object Information Management System in Improving PBB P2 Services - Azmar, Muhammad; Junita, Audia; Kusmanto, Heri (Borong Newinera Publisher, 2025)
The Tax Object Information Management System (SISMIOP) is an innovation in the digitization of tax administration that aims to increase the efficiency, transparency, and accuracy of the management of Rural and Urban Land and Building Tax (PBB-P2). This study aims to analyze the implementation of the SISMIOP policy in the Regional Revenue Agency (Bapenda) of Lalat Regency, identify the factors that affect its success, and evaluate its impact on the improvement of tax services. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show that the implementation of SISMIOP has increased efficiency in collecting data on tax objects, accelerated the payment process, and increased transparency in tax administration. However, there are still several obstacles, such as limited technological infrastructure, resistance from taxpayers, and lack of socialization related to the use of this system. Factors that affect the success of SISMIOP implementation include local government support, human resource readiness, and integration with digital payment services. The impact of the implementation of SISMIOP can be seen from increasing taxpayer compliance, accelerating tax services, and increasing regional tax revenues. This study concludes that although SISMIOP has had a positive impact on improving PBB-P2 services, it is still necessary to strengthen technological infrastructure, increase people's digital literacy, and optimize tax digitization policies to increase the effectiveness of the system in a sustainable manner.